2015
DOI: 10.1186/s13221-014-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

γ-Actin plays a key role in endothelial cell motility and neovessel maintenance

Abstract: BackgroundAngiogenesis plays a crucial role in development, wound healing as well as tumour growth and metastasis. Although the general implication of the cytoskeleton in angiogenesis has been partially unravelled, little is known about the specific role of actin isoforms in this process. Herein, we aimed at deciphering the function of γ-actin in angiogenesis.MethodsLocalization of β- and γ-actin in vascular endothelial cells was investigated by co-immunofluorescence staining using monoclonal antibodies, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
(53 reference statements)
2
25
0
Order By: Relevance
“…Previous studies from our group have demonstrated a role for g-actin in cell polarity and motility 21 and angiogenesis, 22 as well as resistance to microtubule-targeted agents. 23 Microtubule-targeted agents such as the anti-cancer drug paclitaxel, induce mitotic arrest and subsequent cell death.…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies from our group have demonstrated a role for g-actin in cell polarity and motility 21 and angiogenesis, 22 as well as resistance to microtubule-targeted agents. 23 Microtubule-targeted agents such as the anti-cancer drug paclitaxel, induce mitotic arrest and subsequent cell death.…”
Section: Introductionmentioning
confidence: 82%
“…This suggests that under knockdown conditions, cells overexpress one isoform to compensate for loss of the other. This has not been observed for CYA isoforms in other studies, either using the same cocktail of isoform-specific siRNA (Dugina et al, 2009) or using only one of those sequences (Pasquier et al, 2015). This could be due to their use of different cell types, varying doses of siRNA or incubation times, and/or the use of only a single CYA-specific siRNA in one of the studies.…”
Section: Band C-sirna Treatment Induces Isoformspecific Knockdown Imentioning
confidence: 79%
“…These results are consistent with an absolute, albeit dosage-sensitive, requirement for b-CYA in VACV actin nucleation and actin-based motility. Previous studies have also demonstrated significant morphological and functional changes in various cell types with incomplete knockdown of CYA isoforms, such as taking on a less or a more contractile phenotype, or an increase/ decrease in lamellipodial structures, stress fibres, and cell motility (Dugina et al, 2009;Pasquier et al, 2015;Shum, Pasquier, Po'uha, O'Neill, Chaponnier, Gunning, & Kavallaris, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations